(untitled) (Faridpur Medical College Journal, 2016)
Postpartum haemorrhage is the leading cause of maternal mortality worldwide. Total 67-80% of cases are caused by uterine atony. Preventive measures include prophylactic drug use to aid uterine contraction after delivery, thus avoiding severe blood loss and reducing maternal morbidity and mortality. Carbetocin is a synthetic analogue of oxytocin with a long half-life which ensure more effective contraction and less adverse effects. It can be administered as a single dose injection either intravenously or intramuscularly rather than as an infusion over several hours as is the case with oxytocin. Carbetocin is currently indicated for prevention of uterine atony after delivery by caesarean section in spinal or epidural anaesthesia. A reduced need for additional uterotonics was observed with carbetocin vs. oxytocin in high-risk women and carbetocin was at least as effective as syntometrine in low-risk women. Carbetocin is effective treatment for the prevention of postpartum haemorrhage not only following caesarean delivery but also after vaginal delivery in high-risk women and those who suffer from hypertensive disorders in pregnancy. Further research is required to assess whether prophylactic carbetocin is superior to conventional uterotonic agents following vaginal delivery in low-risk women. Faridpur Med. Coll. J. Jul 2015;10(2): 76-83